Understanding COVID-19 Vaccines Today: Are T-cells Key Players? - Areez Shafqat; Tarek Z. Arabi; Belal N. Sabbah; Humzah S. Abdulkader; Shameel Shafqat; Adhil Razak; Junaid Kashir; Khaled Alkattan; Ahmed Yaqinuddin (Vaccines, 2022)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has heavily mutated since the beginning of the coronavirus-2019 (COVID-19) pandemic. In this regard, the so-called variants of concern (VOCs) feature mutations that confer increased transmissibility and evasion of antibody responses. The VOCs have caused significant spikes in COVID-19 cases, raising significant concerns about whether COVID-19 vaccines will protect against current and future variants. In this context, whereas the protection COVID-19 vaccines offer against the acquisition of infection appears compromised, the protection against severe COVID-19 is maintained. From an immunologic standpoint, this is likely underpinned by the maintenance of T-cell responses against VOCs. Therefore, the role of T-cells is essential to understanding the broader adaptive immune response to COVID-19, which has the potential to shape public policies on vaccine protocols and inform future vaccine design. In this review, we survey the literature on the immunology of T-cell responses upon SARS-CoV-2 vaccination with the current FDA-approved and Emergency Use Authorized COVID-19 vaccines.